2006
DOI: 10.1002/clc.4960290105
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sequelae in Brooklyn after the September 11 terrorist attacks

Abstract: Background: Terrorism, such as the attacks on the World Trade Center (WTC) on September 11,2001, result in higher stress‐related disorders, especially in those persons in close proximity. Hypothesis: Cardiac events resulting from the September 11,2001 tragedy have not been detailed near the WTC. Methods: Patients admitted to the Telemetry and Coronary Care Units at New York Methodist Hospital 4 miles from the WTC 60 days prior to and after the September 11 attacks were analyzed. In all, 1,653 admissions were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…Twelve percent of patients experienced a worsening of seizures in the immediate aftermath of 9/11. This study substantiates findings in other studies by Ho et al, 2002 andFeng et al, 2006 demonstrating a strong correlation between physical and psychological stress.…”
Section: Washington District Of Columbia/ Adult Populationsupporting
confidence: 82%
See 1 more Smart Citation
“…Twelve percent of patients experienced a worsening of seizures in the immediate aftermath of 9/11. This study substantiates findings in other studies by Ho et al, 2002 andFeng et al, 2006 demonstrating a strong correlation between physical and psychological stress.…”
Section: Washington District Of Columbia/ Adult Populationsupporting
confidence: 82%
“…This finding was ascertained by reviewing medical records of 1,653 hospital admissions at New York Methodist Hospital in the two months before and after September 11. This study demonstrates that a strong correlation exists between physical and psychological stress (Feng et al 2006).…”
Section: New York City/ Adult Populationmentioning
confidence: 89%
“…Physical health outcomes received substantially less attention, although some research found that survivors and rescue workers in New York reported many physician-diagnosed physical health problems both immediately (Feng, Lenihan, Johnson, & Reddy, 2006;Lampert, Baron, McPherson, & Lee, 2002;Steinberg et al, 2004) and as long as 5 years after 9/11 (Brackbill et al, 2006;Wheeler et al, 2007). Indeed, a growing body of research suggests extremely stressful events may trigger biological processes that increase an individual's risk of developing various health ailments (e.g., gastrointestinal, musculoskeletal, neurological;McEwen, 1998;Pizarro, Silver, & Prause, 2006;Schnurr & Green, 2004).…”
mentioning
confidence: 99%
“…The year following the 9-11 terrorist attack, there were significantly more admissions (p = .008) with MI and tachyarrhythmias based on a retrospective review of charts (n = 1,653) at a hospital within four miles of the disaster site (Feng, Leniham, Johnson, Karri, & Redd, 2006). In a probability sample (n = 2,729, 52.2% female) from the National Health Interview Survey, there was increased relative risk of heart problems nationally at one (2.98, 95% CI = 1.19-7.49, p < .05), two (3.12, 95% CI = 1.37-7.12, p < .01), and three (1.38, 95% CI = 0.55-3.41, p < .001) years following the 9-11 terrorist attack (Holman et al, 2008).…”
Section: Traumatic Eventsmentioning
confidence: 99%